IT Infrastructure for Knowledge Management - Mohd Shukri, Alias; Shyam Bihari, Goyal (INTI International University, 2020)
The relationship between the use of strategic performance measuring strategies (SPMS), organizational learning, information systems (IS) strategic alignment, information technology (IT) information management (KM), competitive use of information resources and organizational performance has been investigated in this study. The researcher used the social science statistics (SPSS) package to analyze the mathematical data. The findings prove that organizational learning and IS strategic alignment have been strongly influenced by SPMS and positively. The methods provided by SPMS as a strategy for communication and dialogue between employees improve the alignment levels of the organization's IS strategy. The results showed that organizational learning and alignment of IS strategies have significant and positive implications for the construction of KM IT infrastructure. Thus, the integration between IS strategy and business strategy through SPMS, appears to improve the targeting and direction of factory members and their interactions improve the construction of IT information management infrastructure.